CLASSIFICATION AND ANALYSIS OF FACTORS INFLUENCING WOUND HEALING RATES - Ismoilov Ibodjon Imomjonovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Have you ever wondered why on some people everything heals “like a dog,” but on others every scratch is a problem? It also happens that injuries do not heal for months and become chronic. We can immediately name at least two reasons for long-term non-healing wounds - age and infection. But in fact, there are many more factors influencing healing. It is traditional to divide the factors influencing wound healing into two groups - general and local.